A formulation for high-fidelity simulations of pool boiling in low gravity. (November 2019) - Dhruv, Akash; Balaras, Elias; Riaz, Amir; Kim, Jungho
Highlights: Multiphase solver with phase changes for boiling simulations in microgravity. Level set based interface tracking with sharp jumps using a Ghost Fluid Method (GFM). Dynamic contact line treatment for modelling wall adhesion. Block structured grid with Adaptive Mesh Refinement (AMR). Fully explicit time advancement using fractional step method. Hybrid multigrid-HYPRE Poisson solver. MPI based parallelization. Validation with existing experiments and published results. 2 nd order overall accuracy. Good agreement with Microheater Array Boiling Experiments (MABE). Cost/efficient tool for high fidelity boiling simulations. Abstract: Direct numerical simulation of pool boiling under varying gravity environments was performed and compared with experimental data. The three dimensional solver is fully explicit in time and uses a fractional step method for Navier-Stokes, energy and mass transfer equations. A level-set technique is used to represent and advect the interface. Sharp jumps are applied to the diffusion terms using a ghost-fluid method and the advection terms are discretized using a third order weighted essentially non-oscillatory scheme. A multi-level, block-structured adaptive mesh refinement is used to selectively refine the grid around the interface and thermal boundary layer. The latter contributes towards accurate calculation of evaporative heat flux. The pressure Poisson solver uses Hypre to solve the linear system on the coarsest level and geometric multi-grid method to prolong-restrict the solution between successive refinements. Parallelization is achieved using MPI on distributed memory systems and a dynamic contact line model is implemented to account for inertial effects on vapor bubbles due to wall adhesion force. Validation cases are presented to test the accuracy of the solver in comparison to analytical and experimental results. Replicability is also demonstrated by comparing results with already published data. A simple mathematical model is used to account for nucleation site density and results of pool boiling simulations are compared with experimental results to illustrate the effects of subcooling and gravity.